The law of iterated logarithm for solutions of stochastic differential equations - Makhno, S. Ya. (Ukrains’kyi Matematychnyi Zhurnal, 1996)
We prove the law of iterated logarithm for solutions of stochastic differential equations with perturbed periodic coefficients.